The effects of inquiry-based experiment-integrated science games among secondary school students - Eylem Bayir; Sefanur Evmez (International Journal of Evaluation and Research in Education (IJERE), 2019)
This study aimed to investigate how inquiry-based experiment-integrated science games affect the achievement and scientific process skills of 5th grade students. The topics of “Light and Sound” and “Electricity in Our Lives” were selected for the experiment. Two groups totaling 41 students participated. The research method consisted of a quasi-experimental design utilizing an experimental and control group. While 21 students in the experimental group played inquiry-based experiment-integrated science games developed by the researchers, no educational game was included in the lessons of the control group of 20 students. “Light and Sound Achievement Test”, “Electricity Achievement Test” and “Science Process Assessment” were applied to both groups in the form of a pre- and post-test. To analyze the data, independent t-test was used. Students in the experimental group were more successful than the control group in their scores for both achievement and scientific process skills. It can be inferred from the results that students develop better achievement and scientific process skills by playing science games. It is recommended that such games should be integrated into the science classroom.